Conservation and Rehabilitation of River Aquatic Resources Affected by Municipal Waste - Cahyono, Indra; Sugihastira, Sugihastira; Tatangin, Sumirna P.; Lengka, Kedis; Hasrul, Hasrul (Indonesian Journal of Coastal and Marine Studies, 2025)
Urban activities are one of the main factors that put significant pressure on river ecosystems through the disposal of domestic waste, industrial waste, and surface runoff that carry various types of pollutants, along with population growth, increased economic activity, and uncontrolled land-use changes. These conditions have an impact on the decline in water quality which is characterized by an increase in the load of organic matter, nutrients, and harmful substances, thereby triggering the degradation of river habitats in the form of excessive sedimentation, damage to riparian vegetation, and changes in the physical structure of river channels, which ultimately lead to a decrease in aquatic biodiversity, both in terms of number and species composition. Many aquatic organisms, such as fish and macrozoobentos, are becoming increasingly vulnerable to pollution and habitat loss, resulting in population declines and even local extinctions. Based on these conditions, this article aims to examine the concept of conservation and rehabilitation of river aquatic resources affected by urban waste through a national literature review approach. The method used is a literature study of Indonesian scientific journals, reference books, and official government documents related to environmental and water resources management. The results of the study show that urban river conservation and rehabilitation efforts require an integrated approach that includes pollution control through effective waste management, restoration of river and riparian habitats, and sustainable management of watersheds, supported by strong environmental policies, consistent law enforcement, and active community participation to ensure the sustainability of the ecological function of rivers